"Women Convicted Under Murder Charges: Case Studies" - Gurmanjit Kaur (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In this paper, women convicted under murder charges lodged in prisons of Punjab (India) have been taken for case studies. Two unique cases of convicted women have been selected for the purpose. One highly educated (married but separated from husband) woman was convicted in murder case; as she had hired a criminal person to murder a higher official working in judiciary (married having children); who was from her family friends and her boy friend before marriage. In the second case, a girl who had lost her parents in childhood murdered her paternal uncle, who was her caretaker after the death of her parents. The girl got involved with a group of gangsters. This very talented girl shot her uncle and commits the crime. These two women have been studied on the basis of a self-prepared questionnaire; containing questions to get information about the reasons to commit the crime, mental status after committing crime - sub-divided under two headings a) about self and b) about fellow inmates, perceptions of the women about the availability of facilities in prisons of Punjab and the attitude of these women towards Rehabilitations programs/ Educational/ Life Skill Development Programs has been examined. A Plan of action for rehabilitation of these women through different Educational, Skill Development and Life Skills Development Program has been prepared.